2015
DOI: 10.1177/1934578x1501000216
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive and Bradycardic Effects of Quinovic Acid Glycosides from Aspidosperma fendleri in Spontaneously Hypertensive Rats

Abstract: The Aspidosperma genus (Apocynaceae) represents one of the largest sources of indole alkaloids widely associated with cardiovascular effects. Aspidosperma fendleri, a plant found mainly in Venezuela, has a single phytochemical report in which is revealed the presence of alkaloids in its seeds. This study explored the cardiovascular effects of an ethanolic extract of A. fendleri leaves (EEAF) in spontaneously hypertensive rats (SHR) and its potential bioactive compounds. Using bioguided fractionation, fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In the present study, Aspidocarpine showed a similar antihypertensive response, but in lower concentrations. In addition, extracts of A. subincanum [ 15 ], A. pyrifolium [ 14 ], A. fendleri [ 13 ], and A. macrocarpum [ 12 ] showed significant hypotensive effects, consistent with the results presented by Aspidocarpine. These reports confirm that the genus Aspidosperma is an important source of alkaloids with cardiovascular activity.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, Aspidocarpine showed a similar antihypertensive response, but in lower concentrations. In addition, extracts of A. subincanum [ 15 ], A. pyrifolium [ 14 ], A. fendleri [ 13 ], and A. macrocarpum [ 12 ] showed significant hypotensive effects, consistent with the results presented by Aspidocarpine. These reports confirm that the genus Aspidosperma is an important source of alkaloids with cardiovascular activity.…”
Section: Resultssupporting
confidence: 74%
“…Many of this species are used in folk medicine for the treatment of malaria [ 8 ], fever [ 9 ], inflammation, diabetes, high blood pressure [ 10 ], and cardiovascular diseases [ 11 ]. In addition, studies carried out with extracts from several species of Aspidosperma showed important antihypertensive effects [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…quinovic acid 3-O-β-rhamnopyranoside (9) and quinovic acid 3-O-βfucopyranoside (10) were isolated. These saponins showed hypotensive and bradycardic activity (Estrada et al, 2015). The species Aspidosperma subincanum and Aspidosperma tomentosum are used by the population in Brazil to treat diseases.…”
Section: -Introductionmentioning
confidence: 99%
“…The genus Aspidosperma is a source of biologically active indole alkaloids (Pereira et al, ) even though other classes of secondary metabolites have been reported (Estrada et al, ). The species A. subincanum Mart.…”
Section: Resultsmentioning
confidence: 99%